Aquifer Investigation in Cibodas Bogor, West Java, Indonesia, using a geoelectrical method and 2D subsurface modeling - rizqi, al hussein flowers; Erlandi, Muhammad; Arifai, Muhammad; Ibnu Hibban, Muhammad (Retii, 2025)
This study was conducted at the location of a cattle pen (Kafeel Farm) in Bogor City, more precisely in the Cibodas village. The purpose of this study is to use subsurface cross-sectional correlations to get a general picture of the lithology, geological structure, and subsurface aquifers. In addition to improving knowledge of the depth and distribution of aquifers in the study area, the contribution of this research will influence residents' groundwater searches. The geoelectrical method with Schlumberger configuration is the methodology employed in this study. In the research area, there were three points of observation in the geolectrical acquisition data. From oldest to youngest, the study area's lithology consists of sandstone with mudstone intercalations (Serpong Formation) and limestone lithology (Bojongmanik Formation). The weathering of limestone and sediments from the Cisadane River is used to interpret the surface soil. At a depth of 8 to 35 meters and a thickness ranging from 10 to 18 meters, the study area's aquifer contains shallow groundwater. Drilling is advised at observation point 2, at a depth of approximately 8 to 18 meters Keyword : Aquifer, Serpong Formation, Bogor, Geoelectrical; Schlumberger